Clean water in the slums of East Africa - Tampu Stelian; Peter Gergo Juhasz (Insights into Regional Development)
Researchers on human security now know that science has to deal with the water issues of our planet, which significantly determines the sense of security of human life. Where is no water, there is no life, so safety is lost. However, where it is present but not of adequate quality, unsafe for the biological organism, it is equally a hazard. As a result of all this, a humanitarian crisis, a catastrophe, and a disaster is developing, which the state bodies must prevent and restore in an ideal situation with the non-governmental organizations and civil society organizations. Africa is most at risk today in this area because it is unable to provide clean water to its slums, but it is also unable to make other infrastructural developments. And to keep human life safe, that is, NGOs must act to give clean water to the people who live there.